An intronic polymorphism of the gene Plakophilin-3 is associated with IVF failure - Joha, Mohamad Sami; Soukkarieh, Chadi; Alhalabi, Marwan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Implantation failure is determined when transferred embryos fail to implant following in vitro fertilization (IVF). In recent years, many studies suggest that implantation failure could be related to several genetic factors. In the current study, authors aimed to investigate the association of PKP3 rs10902158 (G>A) polymorphisms with the risk of implantation failure after ICSI treatment. Methods: 97 women, who underwent ICSI treatment owing to male factor infertility, were prospectively recruited in this cross-sectional study. Genomic DNA was prepared from peripheral blood samples in order to analyze the polymorphism (rs10902158) at the PKP3 gene by PCR-RFLP. The Results were presented as a genotype (GG, GA, and AA), and their relationship to IVF outcome was analyzed. Results: The patients were divided into two groups according to clinical pregnancy: the pregnant group included 51 patients (53%) and the non-pregnant group included 46 patients (47%). The clinical pregnancy outcome was significantly different between genotypes, which was 0%, 45.8% and 58.8% in the patients having the genotype AA, GA and GG respectively (p-value = 0.03). Conclusions: The presence of the allele A of the PKP3 SNP rs10902158 is associated with a reduced clinical pregnancy outcome in the patients undergoing ICSI treatment and may be helpful predictor for implantation failure.